The masses of Neutron Stars - Rocha, Livia Silva (2023)
After almost 60 years since the discovery of the first pulsar, the physics of Neutron Stars (NSs) still present unanswered questions that could lead to a new era in Science. Being the densest and smallest stars observed in the Universe, with average densities above the nuclear saturation density (rho_sat = 2.8 x 10^ g/cm^3), reproducing their matter in terrestrial laboratories is an extremely difficult challenge. The sample of NSs with measured masses is growing thanks to technological and observational advances. The measurement of macroscopic properties of these objects allows us to trace their origins and understand how they are formed. The observed masses reverted the idea of the existence of a canonical value imprinted at birth. The range of masses, much larger than what was previously considered possible, indicates the existence of different evolutionary paths and histories leading to the formation of NSs. In addition, the observation of extremely massive NSs, such as PSR J0952-0607 (m = 2.35 +- 0.17 M_sun) and many other we will comment through this Thesis, has also raised the problem of the maximum mass predicted by General Relativity (GR) combined with a theory of supranuclear matter. The main objective of this Thesis is to study the mass distribution of NSs applying computational methods of Bayesian analysis to make inferences about its shape and the behavior at the high-mass region. In agreement with previous work, we find that the distribution has a bimodal character, that reflects the existence of at least two different populations of NSs. However, contrary to previous results, we show that these objects can reach masses as high as 2.6 M_sun, supporting, for instance, the classification of the less massive component of the GW190814 event, with a mass m=2.59 +- 0.09 M_sun, as a NS. Given the promising scenario of gravitational wave (GW) detection, that can help solving several problems related to the physics of NSs, part of this Thesis was dedicated to create an online catalog of neutron star binary systems (potential sources of GWs when they coalesce), with the aim of studying how these systems are formed, what distinguish those systems that will coalesce from those that will not, at least on a Hubble time, and which are the \"fingerprints\" from these coalescence that can be translated into observable quantities. Finally, in order to contribute to the problem of the nature of matter found in the interior of these stars, this Thesis also presents an equation of state (EOS) model based on the \"strange matter hypothesis\'\' to describe the internal composition of NSs through a gas of quarks in the state known as color-flavor-locking (CFL). The results obtained support the existence of extremely massive NSs, in agreement with statistical results directly inferred from the observed sample.